2014
DOI: 10.1007/s12223-014-0342-2
|View full text |Cite
|
Sign up to set email alerts
|

The oral microbiome diversity and its relation to human diseases

Abstract: As one of the most clinically relevant human habitats, the human mouth is colonized by a set of microorganisms, including bacteria, archaea, fungi, and viruses. Increasing evidence has supported that these microbiota contribute to the two commonest oral diseases of man (dental caries and periodontal diseases), presenting significant risk factors to human health conditions, such as tumor, diabetes mellitus, cardiovascular diseases, bacteremia, preterm birth, and low birth weight in infants. It is widely accepte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
204
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(214 citation statements)
references
References 171 publications
3
204
0
7
Order By: Relevance
“…Oral dysbiosis leads locally to periodontitis, dental caries and potentially to head and neck cancer (Wade, 2013;He et al, 2015). There is also increasing evidence of a role for oral dysbiosis in systemic diseases of the lung (Beck et al, 2012), digestive tract (Ahn et al, 2012) and cardiovascular system (Koren et al, 2011), yet factors that influence the oral microbiome are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Oral dysbiosis leads locally to periodontitis, dental caries and potentially to head and neck cancer (Wade, 2013;He et al, 2015). There is also increasing evidence of a role for oral dysbiosis in systemic diseases of the lung (Beck et al, 2012), digestive tract (Ahn et al, 2012) and cardiovascular system (Koren et al, 2011), yet factors that influence the oral microbiome are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study of primary Sjögren’s syndrome patients with normal salivary flow rate found that the number of bacterial genera and species was lower in patients, and concluded that saliva dysbiosis is a key characteristic of primary Sjögren’s syndrome [20]. Moreover, changes in the oral microbiota are found to be associated with several other diseases including squamous cell carcinoma, atherosclerosis, bacteraemia, and rheumatoid arthritis [21]. …”
mentioning
confidence: 99%
“…Dental caries is a bacterial disease of the dental hard tissues (teeth); it is characterized by a localized, progressive, molecular disintegration of the tooth structure [92,93]. Caries is associated with dental plaque of smooth coronal surfaces, pits, and fissures.…”
Section: Two Pathogenic Bacteria From the Oral Cavity P Gingivalis mentioning
confidence: 99%